All-cause and cause-specific mortality in systemic lupus erythematosus: a population-based study. (19th April 2021) - Moghaddam, Bahar; Marozoff, Shelby; Li, Lingyi; Sayre, Eric C; Zubieta, J Antonio Aviña-
Abstract: Objective: To investigate all-cause and cause-specific mortality in SLE patients between two time periods, 1997–2005 and 2006–14. Methods: We used an administrative health database from the province of British Columbia, Canada to match all incident SLE patients to 10 non-SLE individuals on sex, age and index date. Cohorts were divided into two subgroups, according to diagnosis year: early cohort 1997–2005 and late cohort 2006–14. The outcome was death [all-cause, renal disease, cancer, infection, cardiovascular disease (CVD) and other]. Hazard ratios (HR) and 95% CIs were estimated using univariate and multivariable Cox models. Results: Among 6092 SLE patients and 60 920 non-SLE individuals, there were 451 and 1910 deaths, respectively. The fully adjusted all-cause mortality HR (95% CI) in the overall SLE cohort was 1.85 (1.66, 2.06), with no statistically significant improvement between early and late cohorts [1.95 (1.69, 2.26) vs 1.74 (1.49, 2.04)]. There was excess mortality from renal disease [3.04 (2.29, 4.05)], infections [2.74 (2.19, 3.43)] and CVD [2.05 (1.77, 2.38)], but not cancer [1.18 (0.96, 1.46)], in the overall SLE cohort. There was no statistically significant improvement in cause-specific mortality between early and late cohorts for renal disease [3.57 (2.37, 5.36) vs 2.65 (1.78, 3.93)], infection [2.94 (2.17, 3.98) vs 2.54 (1.84, 3.51)] and CVD [1.95 (1.60, 2.38) vs 2.18 (1.76, 2.71)]. There was no increase in cancer-related mortality in either cohort [1.27 (0.96, 1.69) vs 1.10 (0.82, 1.48)]. Conclusion: This population-based study demonstrates a persisting mortality gap in all-cause and cause-specific deaths in SLE patients, compared with the general population.